The Independent European Central Bank: Keynesian Alternatives - Philip Arestis (Levy Economics Institute of Bard College, 1999)
In this paper, the author aims to question the assumptions underlying the economic case for the independent European Central Bank (ECB) and argues that although a European Clearing Agency (ECA) of the type Keynes envisaged for the international economy is not a panacea for the economic problems of the European Union (EU), it is, nonetheless, a better way forward and far superior to the ECB. The paper (1) outlines the theoretical basis of Keynesian monetary and financial theory; (2) aims to ascertain the extent to which credit availability is affected by the creation of an ECB and, on that basis, to offer a critical analysis of current proposals for an ECB; (3) looks closely at the case for the ECA, seen as performing a range of functions rather than having a remit defined simply in terms of strict monetary control, including a commitment to providing the necessary finance for full employment and a responsibility for ensuring that the burden of balance-of-payments adjustment falls upon both deficit and surplus countries.
Keywords: 330